Interleukin-6 serum level and gene polymorphism in keloid patients - Abdu Allah, Azza Mohamed Kamel; Mohammed, Kawthar Ibraheem; Farag, Azza Gaber Antar; Hagag, Magda Mostafa; Essam, Mai; Tayel, Nermin Reda (Cellular and Molecular Biology, 2019)
The formation of keloid is associated with accumulation of extracellular matrix (ECM) formed mainly of collagen and fibronectin. Persistent deregulated IL-6 synthesis causes the development of various diseases. This study aim to investigate interleukin 6 (IL-6) serum level and gene polymorphism in a sample of Egyptian patients having keloid. This study was carried out on 90 subjects; 60 patients with keloid, and 30 age and sex matched apparently healthy control. All subjects underwent full history taking, clinical examinations, weight and length measuring to calculate BMI, dermatological examination, analysis of IL6-572 gene polymorphism using REFLP- PCR and IL-6 serum level using ELISA.IL-6 serum levels were significantly higher in keloid patients than control group (75.54±39.18) vs (19.17±6.06), (p <0.001). The higher serum levels of IL-6 were associated with GG genotype (104.84±19.12) followed by CG (57.64±35.38) genotype (P<0.001). GG genotype was significantly higher in keloid patients and increased the risk for keloid development by nearly14 folds (p<0.001, OR (95%CI) =13.81). CG genotype was significantly observed in keloid patients and increased the risk for keloid development by about 4 times (p=0.010, OR (95%CI) =4.27). G Allele significantly increased the risk for keloid development by about 5 folds (P <0.001 OR =5.11). In conclusion, there was a great association between IL-6 572 gene polymorphism and its serum level in patients with keloid specifically who have family history.